Gold wrist-assisted PFNA reduces internal complications and enhances recovery in obese osteoporotic patients with intertrochanteric femur fractures - Zhonghan Wu; Jianyang Li; Shitan Mao; Jingtao Lu; Yao Zhao; Shuisheng Yu; Dasheng Tian; Juehua Jing; Rongguang Ao; Xinzhong Xu (PLoS ONE, 2026)
Introduction Obese, osteoporotic patients with intertrochanteric fractures face higher surgical risks and delayed recovery. The “Gold Wrist,” an auxiliary curved guiding instrument for proximal femoral nail anti-rotation (PFNA), was developed to assist guidewire placement and improve procedural efficiency. Methods In this retrospective cohort study, 500 patients (almost all with BMI > 28 and varying degrees of osteoporosis) underwent PFNA using either the Gold Wrist (n = 250) or conventional instruments (n = 250). Outcomes included operative time, fluoroscopy exposure, incision length, inflammatory markers, functional recovery, internal medicine complications, mechanical complications, hospitalization cost, and estimated carbon footprint. Finite element analysis assessed device mechanical stability. Results Finite element analysis confirmed reliable mechanical performance. The Gold Wrist group had shorter operative time (114.7 ± 34.6 vs. 127.3 ± 34.3 min), smaller incisions (6.15 ± 1.88 vs. 7.27 ± 1.79 cm), and lower TNF-α, IL-6, CRP, and CK levels (all P < 0.0001). Functional recovery was faster, with higher Harris Hip Scores (87.7 ± 2.7 vs. 84.7 ± 3.4) and greater hip motion. Internal medicine complications—including infection, deep vein thrombosis, pulmonary embolism, and cardiovascular events—were significantly reduced. Mechanical complications, including implant failure, were reported separately. Hospitalization costs and estimated carbon footprint were also lower. Conclusion The auxiliary Gold Wrist device improves surgical precision, accelerates recovery, and reduces internal medicine complications in obese, osteoporotic patients undergoing PFNA. It offers a clinically effective and sustainable approach to managing high-risk intertrochanteric fractures.